2014
DOI: 10.1021/ja5006465
|View full text |Cite
|
Sign up to set email alerts
|

A Metal–Organic Framework-Based Material for Electrochemical Sensing of Carbon Dioxide

Abstract: The free primary hydroxyl groups in the metal-organic framework of CDMOF-2, an extended cubic structure containing units of six γ-cyclodextrin tori linked together in cube-like fashion by rubidium ions, has been shown to react with gaseous CO2 to form alkyl carbonate functions. The dynamic covalent carbon-oxygen bond, associated with this chemisorption process, releases CO2 at low activation energies. As a result of this dynamic covalent chemistry going on inside a metal-organic framework, CO2 can be detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
157
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(159 citation statements)
references
References 76 publications
2
157
0
Order By: Relevance
“…[203] It is shown that the diffusion of CO2 into the extended framework of CD-MOF-2 resulted in the formation of alkyl carbonic acid functions on the γ-CD, by covalent bonding to non-coordinated free primary hydroxyl groups, affording CA-CDMOF-2. [204] While there has been a lot of data on CO2 sequestration, there has been only one report using colorimetric sensing, and no reports of electrochemical sensing of CO2 by bioMOFs and also in MOFs. [204] The authors employed electrochemical impedance spectroscopy to measure the changes in proton conductivity, and after observing a large drop in conductivity (approximately 550 fold) following infusion of CO2 in CDMOF-2, associated this with the impediment in motility of free protons.…”
Section: Co2 Capturementioning
confidence: 99%
See 3 more Smart Citations
“…[203] It is shown that the diffusion of CO2 into the extended framework of CD-MOF-2 resulted in the formation of alkyl carbonic acid functions on the γ-CD, by covalent bonding to non-coordinated free primary hydroxyl groups, affording CA-CDMOF-2. [204] While there has been a lot of data on CO2 sequestration, there has been only one report using colorimetric sensing, and no reports of electrochemical sensing of CO2 by bioMOFs and also in MOFs. [204] The authors employed electrochemical impedance spectroscopy to measure the changes in proton conductivity, and after observing a large drop in conductivity (approximately 550 fold) following infusion of CO2 in CDMOF-2, associated this with the impediment in motility of free protons.…”
Section: Co2 Capturementioning
confidence: 99%
“…[204] While there has been a lot of data on CO2 sequestration, there has been only one report using colorimetric sensing, and no reports of electrochemical sensing of CO2 by bioMOFs and also in MOFs. [204] The authors employed electrochemical impedance spectroscopy to measure the changes in proton conductivity, and after observing a large drop in conductivity (approximately 550 fold) following infusion of CO2 in CDMOF-2, associated this with the impediment in motility of free protons. [204] Decrease in the conductivity of CA-CDMOF-2 can be attributed to the loss of coordinated hydroxide that catalyzes the deprotonation of the methanolic medium, blocking of hydrophilic triangular shaped β-windows, therefore decreasing the mass transfer of the intermedium molecules.…”
Section: Co2 Capturementioning
confidence: 99%
See 2 more Smart Citations
“…The CO 2 sensors that were fabricated based on this principle were capable of measuring CO 2 concentrations quantitatively. 161 Figure 2.25 also shows the cyclic change of conductivity of the CD-MOF with sequential CO 2 absorption and desorption. The plot of average conductivity value vs. CO 2 concentration shows that the sensitivity of the conductivity change is relatively high at low CO 2 concentrations.…”
Section: Electrochemical Sensors With Metal-organic Coordination Polymentioning
confidence: 99%